THEOLOGY OF MINISTRY TO THE URBAN POOR WITH SPECIAL CONTEXT OF EMERGING URBAN SLUMS OF VIZIANAGARAM, ANDHRA PRADESH, INDIA - Dr. Srinivasa Rao Chepa (Galaxy International Interdisciplinary Research Journal, 2022)
God looks at the rich and poor equally and both need the salvific experience in God. Gospel is real good news for the poor, because they are looking for equality and dignity. It is important that we realize that God insists that we need to share our resources with the needy and the marginalized. However, Jesus looked at the people differently, and accepted the religious, social, economic and cultural outcaste groups and transformed their lives The Slum Dwellers of Vizianagaram are also socio-economically challenged and backward. Politically they have very little or no voice at all. In the context of the urban poor, the occupation, lifestyle and behavioral patterns of the slum dwellers make them distinct from others in society. Thus, they are considered outcastes, sinners and oppressed in the society without dignity and identity in the society. The urban middle class man does not even consider them as the citizens of the city, and treat them as unwanted elements. A total indifference to the needs of community development in the slums is to evade the Church’s ethical responsibility of Christian social involvement. The church has a better option to play its role and active involvement in eradicating the poverty, oppression and social degradation of the slum dwellers. In reflecting upon the Christian response to human need , church should have recognized the central place of the local church as the vehicle for communicating the Gospel of Jesus Christ both in word and deed.